Assessing the extent to which front-of-pack labelling regulations could support healthy eating among Canadians - Jennifer J. Lee; Christine Mulligan; Hayun Jeong; Mary R. L’Abbé (PLoS ONE, 2025)
Canada mandated front-of-pack labelling (FOPL) regulations, requiring pre-packaged foods meeting and/or exceeding thresholds for nutrients-of-concern (saturated fat, sugars, sodium) to display a ‘High in’ nutrition symbol. Although FOPL regulations align with one of the recommendations of Canada’s food guide (CFG), there is limited evidence on how well the regulations could support healthy eating among Canadians. The objective of this study was to evaluate the Canadian pre-packaged food supply according to FOPL regulations and to assess the extent to which the regulations could support healthy eating among Canadians using the Canadian Food Scoring System (CFSS), a nutrient profile model based on the recommendations of CFG. Using a branded food composition database (n = 17,008), pre-packaged foods were categorized according to FOPL regulations and the CFSS. According to FOPL regulations, approximately 54% of pre-packaged foods would display a ‘High in’ nutrition symbol for meeting and/or exceeding thresholds for at least one nutrient-of-concern. According to the CFSS, approximately 53% of foods were a ‘poor’ or ‘very poor’ choice, while 25% were a ‘good’ or ‘excellent’ choice. Foods that would not display a ‘High in’ nutrition symbol showed significant variation in their healthfulness, with 45% containing low amounts of nutritious foods recommended by CFG. Our findings highlight that many pre-packaged foods in Canada do not represent healthy choices. Although many of these foods will be highlighted with a ‘High in’ nutrition symbol when FOPL regulations are implemented, many foods that would not display a ‘High in’ nutrition symbol do not align well with the recommendations of CFG, particularly those with a variety of multiple ingredients (e.g., many breads, breakfast cereals, combination dishes). Additional tools and strategies are required to support Canadians make healthy food choices.